2023
DOI: 10.3389/fonc.2023.1149599
|View full text |Cite
|
Sign up to set email alerts
|

Intact glycopeptides identified by LC-MS/MS as biomarkers for response to chemotherapy of locally advanced cervical cancer

Abstract: ObjectiveFor locally advanced cervical cancer (LACC), patients who respond to chemotherapy have a potential survival advantage compared to nonresponsive patients. Thus, it is necessary to explore specific biological markers for the efficacy of chemotherapy, which is beneficial to personalized treatment.MethodsIn the present study, we performed a comprehensive screening of site-specific N-glycopeptides in serum glycoproteins to identify glycopeptide markers for predicting the efficacy of chemotherapy, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Li et al. ( 80 ) have recently demonstrated a study to identify glycopeptide markers in serum glycoproteins that can predict the efficacy of chemotherapy for locally advanced cervical cancer (LACC), thus enabling personalized treatment. They conducted a comprehensive screening of site-specific N-glycopeptides in serum samples from LACC patients before and after neoadjuvant chemotherapy (NACT).…”
Section: Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al. ( 80 ) have recently demonstrated a study to identify glycopeptide markers in serum glycoproteins that can predict the efficacy of chemotherapy for locally advanced cervical cancer (LACC), thus enabling personalized treatment. They conducted a comprehensive screening of site-specific N-glycopeptides in serum samples from LACC patients before and after neoadjuvant chemotherapy (NACT).…”
Section: Proteomicsmentioning
confidence: 99%
“…High levels of these glycopeptides indicated chemotherapy effectiveness. The authors suggested that theses six N-glycopeptides may serve as potential biomarkers for predicting the efficacy of chemotherapy in cervical cancer ( 80 ).…”
Section: Proteomicsmentioning
confidence: 99%
“…4–6 In the case of cancer, it is beneficial to discover biomarkers of the inflammatory process in addition to the qualitative and quantitative identification of cancer-specific biomarkers. 7–11 According to Brenner et al , these biomarkers include acute-phase proteins, reactive oxygen and nitrogen species, immune-related effectors, cytokines or chemokines, mediators and prostaglandins, and cyclooxygenase-related factors. 12 The cancer cell type is a promising contender for next-generation biomarkers for applications in surveying treatment responses or unfavourable cases, diagnosis and toxicology.…”
Section: Introductionmentioning
confidence: 99%